Bioactive, Degradable and Tough Hybrids Through Calcium and Phosphate Incorporation - Tallia, Francesca; Ting, Hung-Kai; Page, Samuel J.; Clark, Joshua P.; Li, Siwei; Sang, Tian; Russo, Laura; Stevens, Molly M.; Hanna, John V.; Jones, Julian R. (Frontiers in Materials, 2022)
We report the first inorganic/organic hybrids that show outstanding mechanical properties (withstanding cyclic loading) and bone bioactivity. This new hybrid material may fulfil the unmet clinical need for bioactive synthetic bone grafts that can withstand cyclic loading. A SiO2/PTHF/PCL-diCOOH sol-gel hybrid system, that combined inorganic and organic co-networks at the molecular level, previously demonstrated unprecedented synergy of properties, with excellent flexibility and promoted formation of articular cartilage matrix in vitro. Here, for the first time, calcium and phosphate ions were incorporated into the inorganic component of the hybrid network, to impart osteogenic properties. Calcium methoxyethoxide and triethyl phosphate were the calcium and phosphate precursors because they allow for incorporation into the silicate network at low temperature. The hybrid network was characterised with ATR-FTIR, XRD and solid-state NMR, which proved calcium and phosphate incorporation and suggested the Ca2+ ions also interacted with PCL-diCOOH through ionic bonds. This resulted in an increased strength (17-64 MPa) and modulus of toughness (2.5-14 MPa) compared to the original SiO2/PTHF/PCL-diCOOH hybrid material (which showed strength of ˜3 MPa and modulus of toughness of ˜0.35 MPa), while also maintaining the ability to withstand cyclic loading. The presence of calcium and phosphates in the silicate network resulted in a more congruent dissolution of the inorganic and organic co-networks in TRIS buffer. This was shown by the presence of silicon, calcium and phosphate ions along with PCL in the TRIS buffer after 1 week, whereas Ca-free hybrids mainly released PCL with negligible Si dissolution. The presence of calcium and phosphates also enabled deposition of hydroxycarbonate apatite following immersion in simulated body fluid, which was not seen on Ca-free hybrid. All hybrids passed cell cytotoxicity tests and supported pre-osteoblast cell attachment. The phosphate-free hybrid showed the best mechanical behaviour and supported better cell attachment, spreading and potentially differentiation of cells. Therefore, the SiO2-CaO/PTHF/PCL-diCOOH hybrid represents a promising biomaterial for use in bone regeneration.